Wet-cold preservation of West African yam (Dioscorea spp.) pollen - Daniel, I.O.; Ng, N.Q.; Tayo, T.O.; Togun, A.O. (Cambridge University Press, 2002)
Hermetic cold storage without previous drying (wet–cold storage) was experimented for the preservation of yam pollen grains. Pollens collected from white yam D. rotundata and a wild relative, D. praehensilis, were stored at -80, -20, 5, and 150C in sealed packs for 2 years. Pollen samples were drawn for in vitro germination tests after 100 and 700 days, and hand pollination was conducted after 365 and 730 days in storage. Pollen germination responses were not significantly different among the two species. Though pollen maintained germination capacity at all the storage temperature regimes, there was a significant loss in the viability of pollen stored at 5 and 15 _C after 100 days of storage. After 700 days in storage, pollens stored at 5 and 150C had lost germination capacity while there were no significant differences in the germination of fresh pollen and pollen frozen at -80 and -200C. Hand pollination with pollen of D. rotundata frozen at -800C for 365 days gave 69.5% fruit set and 50% fruit set after 730 days in storage. From these results, the wet–freeze procedure appears promising to execute the establishment of pollen gene banks for yam breeding and for conservation of haploid gene pool of yams in base collections. A pollen storage protocol based on the procedure is recommended.